Odpowiedź:
[tex]log_a x = 2[/tex] ⇔ [tex]\frac{1}{log_x a} = 2[/tex] ⇔ [tex]log_x a = \frac{1}{2}[/tex]
[tex]log_b x =3[/tex] ⇔ [tex]\frac{1}{log_x b} = 3[/tex] ⇔ [tex]log_x b = \frac{1}{3}[/tex]
[tex]log_c x = 6[/tex] ⇔ [tex]\frac{1}{log_x c} = 6[/tex] ⇔ [tex]log_x c= \frac{1}{6}[/tex]
więc
[tex]log_{abc} x =[/tex] [tex]\frac{1}{log_x (a*b*c)}[/tex] = [tex]\frac{1}{log_x a + log_x b + log_x c}[/tex] = [tex]\frac{1}{\frac{1}{2} + \frac{1}{3} + \frac{1}{6} }[/tex] = [tex]\frac{1}{1} = 1[/tex]
Szczegółowe wyjaśnienie: